Motion control of mobile autonomous robots using non-linear dynamical systems approach - Ribeiro, A. Fernando (2017)
This paper presents a solution to the problem of motion control of an autonomous robot, moving in a dynamical and unstable environment. It is based on non-linear dynamical systems, modelling the state variables that define the motion of a robot under an omnidirectional platform, like its direction of navigation and velocity. The approach used, is based on a set of non-linear differential equations that model the evolution of state variables along time, based on the concept of attractors and repellers. In the official RoboCup Middle Size League field, a target is used to attract the robot to a certain position (could be the ball or a desired position to receive the ball), while a repeller could move the robot away from its original path (given by obstacles in the surrounding environment). The research was firstly carried out in a computational simulation environment and later on with robots in a real environment